UTILIZATION OF LIQUID ORGANIC FERTILIZER BASE ON COW (Bos taurus) URINEAS HYDROPONIC NUTRITION IN PAKCOY (Brassica chinensis L.) PLANT - Selva Dena Nusima; Violita Violita (Universitas Negeri Padang, 2020)
Abstract. Pakcoy (Brassica chinensis L.) is a type of vegetable consumed by many people because of its high nutritional content. The obstacle in producing pakcoy is that the land for farming decreases as population growth grows. One way to overcome this is to plant hydroponics by utilizing cow urine as nutrition. This study studied liquid nutrients made from cow urine (Bos taurus) as hydroponic nutrition in the growth of Pakcoy (Brassica chinensis L.) plants. This research is an experimental study. The design used was a completely randomized design with 5 assemblies and 4 replications namely K (AB Mix 10 mL / L air), P1 (8 mL / L air), P2 (10 mL / L cow urine), P3 (cow urine) 12 mL / L air), P4 (cow urine 14 mL / L). The data obtained were analyzed using Analysis of Variance ANOVA. The parameters considered were tall plants, number of leaves, wet weight and dry weight. The results showed the facts about the conservation of hydroponic nutrition of organic fertilizers made from cow urine provided were not significantly different and could not increase the growth of pakcoy (Brassica chinensis L.) plants.Keywords: Pakcoy, Hydroponics, Cow Urine.